Identifying financially remote First Nations reserves - Heng Chen; Walter Engert; Kim P. Huynh; Daneal O'Habib (Bank of Canada, 2022)
Chen et al. (2021) show that almost one-third of First Nations band offices in Canada are within 1 kilometre (km) of an automated banking machine (ABM) or financial institution (FI) branch and more than half are within 5 km. Further, over three-quarters of band offices are within 20 km of an ABM or FI branch and almost 90% are within 50 km. We focus on 49 First Nations locations that are more than 100 km away from an ABM or FI branch or do not have an identifiable travel route (by road or boat) to an ABM or FI branch. We refer to these First Nations as financially remote. We show that these locations have small populations and limited access to internet and mobile services. As a result, these First Nations have poor access to cash sources and physical delivery of financial services as well as limited access to digital payments and electronic banking. We also assess the remoteness of these locations according to an alternative method based on measures of agglomeration (community population) and proximity to other communities. We find that, according to this measure, these 49 financially remote First Nations are generally among the most geographically remote communities in Canada. Further, we show that these First Nations are also among the lowest scoring communities in Canada according to a measure of community well-being based on indicators of educational attainment, labour force activity, income and housing. The geographical remoteness of these 49 First Nations, their small populations, limited infrastructure and digital services, and relatively low community well-being all likely contribute to their poor access to cash and financial services.
Keywords: E; E4; E41; E42; E5; G21; 330; Bank notes; Digital currencies and fintech; Financial institutions; Financial services; Payment clearing and settlement systems